Media Kahoot dalam Model Pembelajaran Team Accelerated Individualization (TAI) untuk Meningkatkan Keaktifan dan Hasil Belajar Peserta Didik - Septiana, Dheka; Utomo, Supri Wahyudi; Styaningrum, Farida (Universitas Nusantara PGRI Kediri, 2026)
The research aims to prove that the use of Kahoot media in the TAI model is able to increase the activity and learning outcomes of students. This study took the form of Classroom Action Research (CAR) and was conducted in class XI PKM SMK Cendekia Kota Madiun with 13 students and involving cash management subject educators. The data analysis techniques used were tests and observations. The results of the study show that 1) The application of Kahoot media with TAI type cooperative learning was proven to run optimally in increasing active student participation. The active participation of class XI PKM SMK Cendekia Kota Madiun students in the petty cash material increased from an average of 50 (quite active) in cycle I to 79 (active) in cycle II. The interactive Kahoot media and appropriate learning model created a comfortable, conducive and competitive learning environment. 2) Student learning outcomes also experienced significant changes, with an increase of 85% in cycle II. The combination of Kahoot media and the TAI model helped students better understand the material through teamwork, individual learning, and interesting evaluations, thereby increasing learning motivation.